Global Multinationals from International Marketing to Folkmarketing: Cultural Identity Through Consumption in Brazil´s Countryside “São João” (Revista Internacional de Folkcomunicação, 2022)
This paper discusses how multinationals, like the US Johnson & Johnson, PepsiCo and Danone, adopt organizational communication strategies centered on Folkmarketing in order to attract the consumer's attention of the Brazilian Northeast countryside. This segment of the population represents about fifty million inhabitants and historically carries the most impoverished of the country area of the country. But even with this stigma, its GDP is Similar to Chile´s and it has very particular traditions, such as St. John's. Through this festival these corporations seek a rapprochement with their target -. Developing activities in the city of Caruaru, inside the state of Pernambuco, known as the "Capital of Forró", referring to the typical musical rhythm of this celebration. We expose, therefore, as the city was known nationally for this nickname and the role of the Globo Television Network, one of the largest broadcasters in the world, in scheduling reports on the festivities and spread of this imaginary.